2017
DOI: 10.1016/j.addbeh.2017.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Chinese Internet Gaming Disorder Scale

Abstract: To develop a consensus on the definition and measurement of Internet gaming disorder (IGD), several recent studies have used the DSM-5's proposed criteria for IGD as the basis in scale construction. This study contributes to this emerging consensus by developing and validating a new Chinese Internet Gaming Disorder Scale (C-IGDS) based on the DSM-5 criteria. A representative sample of Hong Kong community adults (n=502, 50% men, mean age=37.1, age range=18-60) was recruited for a telephone survey with random di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 37 publications
3
62
1
3
Order By: Relevance
“…Although the internal consistency between findings in the present study and others are comparable [15][16][17][18], the present study revealed relatively high floor effects (21%) as compared with previous studies [11,17]. More specifically, another study using a Hong Kong population using C-IGDS showed the floor effect at 0.8%; one study on Iranian population using IGDS-SF9 also showed the floor effect at 0.8% [17].…”
Section: Igds-sf9supporting
confidence: 53%
See 3 more Smart Citations
“…Although the internal consistency between findings in the present study and others are comparable [15][16][17][18], the present study revealed relatively high floor effects (21%) as compared with previous studies [11,17]. More specifically, another study using a Hong Kong population using C-IGDS showed the floor effect at 0.8%; one study on Iranian population using IGDS-SF9 also showed the floor effect at 0.8% [17].…”
Section: Igds-sf9supporting
confidence: 53%
“…Therefore, the validation of an ultrabrief instrument (with less than 10 items) will greatly reduce the administrative burden and the time cost of conducting such assessment. A brief instrument (i.e., the Chinese Internet Gaming Disorder Scale; C-IGDS) was recently developed in Hong Kong [11]. The C-IGDS showed promising psychometric properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A score of 5 is taken as the cutoff point for defining IGD. The Chinese version was found to have good psychometric properties [33,34]. It has been applied in a number of studies [33][34][35].…”
Section: Methodsmentioning
confidence: 99%